2008
DOI: 10.1080/10942910701673493
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nutritional Characteristics of the Horse-Eye Bean [Mucuna Urens (L.) Medik] Subjected to Different Processing Methods

Abstract: The effect of processing methods (autoclaving, cooking, roasting, and germination) on the nutritional characteristics of seeds of Mucuna urens are evaluated. Results indicate that processing methods significantly (p < 0.05) affect the crude protein content of Mucuna beans. Thermal processing results in low levels of methionine, cystine, lysine, and antinutritional factors (HCN, oxalate, phytate, and tannins), but increases the levels of copper and zinc. Proximate compositions differ significantly (p < 0.05) am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(24 reference statements)
1
4
1
Order By: Relevance
“…Nutrient composition and sensory profile of differently cooked green leafy vegetables (conventional, pressure, and microwave cooking) changed during the processing. [5,8] Thus, all cooked vegetables had antioxidant properties similar to some extent to what was found in our studies. The steam cooking did not dramatically affect the antioxidant properties of the vegetables, and in our data only boiling for 10 min slightly changed these properties.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nutrient composition and sensory profile of differently cooked green leafy vegetables (conventional, pressure, and microwave cooking) changed during the processing. [5,8] Thus, all cooked vegetables had antioxidant properties similar to some extent to what was found in our studies. The steam cooking did not dramatically affect the antioxidant properties of the vegetables, and in our data only boiling for 10 min slightly changed these properties.…”
Section: Discussionsupporting
confidence: 87%
“…The health properties of these natural products depend mainly on their phenolic compounds and to a lesser degree on dietary fibers. [1][2][3][4][5][6] Among the frequently used vegetables, [7][8][9][10][11] onions (Allium cepa) are the best known. [12,13] The consumption of these vegetables goes back to ancient times, however, only recently have scientific investigations showed that onion extracts are effective in the prevention of cardiovascular disease due to their hypocholesterolemic, hypolipidemic, antihypertensive, antidiabetic, antithrombotic, and antihyperhomocysteinemia effects.…”
Section: Introductionmentioning
confidence: 99%
“…[34] Quinteros et al [35] reported that all the cooking procedures reduced the soluble oxalate contents in pulses, but microwave and industrial procedures were found more effective than the traditional domestic cooking. Thermal processing has also been shown to reduce the anti-nutritional factors (HCN, oxalate, phytate and tannins) in the horse-eye beans [Mucuna urens (L.) Medik] [36] and in Phaseolus vulgaris. [37] Spinach has been regarded as a high-risk food for individuals susceptible to kidney stone formation due to its capability in increasing the excretion of urinary oxalates.…”
Section: Resultsmentioning
confidence: 99%
“…The higher loss of oxalate content in toasted tigernut might be attributed to the destruction of the oxalate at higher temperature. Umoren et al (2008) reported that thermal processing results in low levels of methionine, cystine, lysine and antinutritional factors (HCN, oxalate, phytate and tannins).…”
Section: Resultsmentioning
confidence: 99%